A pandemic and economic slowdown: the case of India. Issue 19 (21st April 2022) - Chakrabarty, Manisha; Mukherjee, Subhankar
ABSTRACT: In this article, we use a novel dataset on new investment projects undertaken, available for states in India in quarterly frequency, to forecast economic activities in the wake of the ongoing Covid-19 pandemic. Panel data estimates for the country, employing fixed effect and Generalized Method of Moments, show a drop of approximately 50% in investment count during the financial years 2019–20 to 2021–22, compared to the counterfactual projection of an increase of 38% over the same period. State-level analysis reveals similar patterns, even though with considerable heterogeneity – relatively economically well-developed states may witness higher reduction in investment compared to the less developed ones. Given that incidence of Covid cases is also relatively higher in the more developed states, our findings can help in formulating policies appropriate for each state. This study can be generalized in the following three ways: it can be extended over a longer period of time, it can be applied in future crisis periods, and it can be made more precise given more granular data is available.